Students’ Ethical Awareness and Behavior Intentions in the Use of AI Tools: A Proposed Framework - Shrestha, Nabin Kumar (BIC Journal of Management, 2025)
Artificial intelligence (AI) is a mixture of different tools in education that includes transformative opportunities and significant ethical challenges. Even if students are using these AI tools more frequently, it remains unknown how well they understand the ethical implications of doing so. This review summarises the body of research on behavioural intentions of students and ethical awareness regarding the usage of AI in the classroom. Drawing upon studies employing diverse methodologies—such as surveys, qualitative analyses, and experimental designs, the paper examines how students perceive and respond to ethical considerations surrounding AI. Key influencing factors in ethical decision-making are identified, including individual perceptions, institutional policies, and socio-cultural contexts—areas that remain underexplored, particularly in Nepal. The review indicates the need for focused interventions since it shows a gap between students’ understanding of AI ethics and their regular use of moral behaviour. A conceptual framework created during the review process is suggested by the study as a solution to this problem. This method highlights that ethical behaviour, environmental factors, and knowledge interact dynamically. It emphasises the need for rule-based ethical education, clear policy, and a subject-related approach to regulating responsible AI. The result calls on educators, academic schools, and policymakers to use evidence-based rules that help to close the gap between ethical awareness and ethical proactive in AI-embedded learning environments.